2016
DOI: 10.1016/j.cobeha.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Early life exposure to obesogenic diets and learning and memory dysfunction

Abstract: Obesogenic dietary factors, such as simple sugars and saturated fatty acids, have been linked to memory impairments and hippocampal dysfunction. Recent evidence suggests that the brain may be particularly vulnerable to the effects of obesogenic diets during early life periods of rapid growth, maturation, and brain development. Investigations utilizing rodent models indicate that early life exposure to “high fat diets” (40-65% kcal derived from fat) or simple sugars (sucrose or high fructose corn syrup) can imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 77 publications
5
59
0
Order By: Relevance
“…More importantly we highlight the increased sensitivity of the dopamine system during adolescence to the deleterious effects of a diet that is inadequate in protein. Adolescence is characterized by important maturation events within dopamine circuitry and dopamine-related processes [47][48][49][50][51][52] and numerous studies have now demonstrated that adolescence is an important vulnerability window for diet-related alterations of cognitive and neurobiological functions [42][43][44][45][46]. How protein restriction during adolescence may have different, and potentially long-term, impacts on dopamine-related behaviors considering its opposite effects on the mesolimbic and nigrostriatal pathways remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly we highlight the increased sensitivity of the dopamine system during adolescence to the deleterious effects of a diet that is inadequate in protein. Adolescence is characterized by important maturation events within dopamine circuitry and dopamine-related processes [47][48][49][50][51][52] and numerous studies have now demonstrated that adolescence is an important vulnerability window for diet-related alterations of cognitive and neurobiological functions [42][43][44][45][46]. How protein restriction during adolescence may have different, and potentially long-term, impacts on dopamine-related behaviors considering its opposite effects on the mesolimbic and nigrostriatal pathways remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Early life periods like childhood and adolescence are periods of particular vulnerability to the deleterious impact of various diets on corticolimbic circuits and reward-related processes [40][41][42][43][44][45][46]. Interestingly, the dopamine system undergoes delayed maturation taking place during adolescence making it vulnerable to external insults [46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a diet rich in saturated fats [52] as well as intracerebral ventricular injections of saturated fatty acids [53] stimulated microglial activation and inflammatory responses. Previous clinical research [54, 55] and results from experimental mouse models [56] showed that diets high in saturated fat and simple sugars lead to cognitive impairments. Obesity has also reported to induce microglial activation and IL-1R-mediated deficits in hippocampal synaptic plasticity in mice [57].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first investigation of how added sugars affect the gut microbiome during the juvenile and adolescent period of development, during which the brain is particularly vulnerable to the effects of sugar and other dietary factors (44). However, the effects of added dietary sugars on gut microbial populations have been investigated in adult rodents.…”
Section: Figurementioning
confidence: 99%